Participatory Leadership of the Madrasah Principal in Addressing Bullying Cases in Schools (A Case Study at MTs Alkhairaat Sigimpu) - Rani Feranika; Sagaf S. Pettalongi; Jihan Jihan (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2026)
This study examines participative leadership by the head of MTs Alkhairaat Sigimpu as an effective approach to addressing bullying through the collective empowerment of school stakeholders in a systematic and integrated manner. A qualitative case study approach was employed. Data were collected through participant observation, in-depth interviews with the head of the madrasah, teachers, and guidance and counseling teachers, as well as documentation. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that bullying at the school takes both verbal and non-verbal forms. Verbal bullying includes teasing, threats, and rumor spreading among students, while non-verbal bullying involves social exclusion, threatening gestures, and damage to peers’ belongings. In addressing these issues, the head of the madrasah applies participative leadership by involving teachers and counseling staff in collective decision-making. This includes formulating anti-bullying policies, establishing intervention and mediation procedures, and implementing prevention programs through socialization and integrated supervision. Such collaborative involvement fosters a shared sense of responsibility in creating a safe and bullying-free learning environment.